Formulation, Optimization, and Evaluation of Lornoxicam Medicated Chewing Gum Using Ion Exchange Resin Taste Masking - Shah, Kinjal; Joshi, Hemani; Shah, Shailvi; Mehta, Tejal (International Journal of Pharmaceutical Investigation, 2026)
Background This study aimed to develop and evaluate a taste-masked Medicated Chewing Gum (MCG) of Lornoxicam (LXM) using Kyron T-114, a weak cation exchange resin, to improve palatability and patient compliance. LXM, a potent non-steroidal anti-inflammatory drug, suffers from poor acceptability due to its bitterness, making it a suitable candidate for resin-based complexation. Materials and Methods The drug-resin interaction was optimized by varying resin activation, drug-to-resin ratio, pH, swelling time, and stirring conditions, achieving a maximum drug loading of 81.59% at a 1:2 ratio. The optimized complex was incorporated into a chewing gum base and characterized for physicochemical, mechanical, and performance attributes. Differential scanning calorimetry and Fourier transform infrared spectroscopy confirmed drug-resin complexation and excipient compatibility. Results and Discussion The optimized formulation exhibited good flow properties, hardness, adhesiveness, and uniformity, with friability below 1% and drug content of 98.24±1.23%. In vitro studies demonstrated rapid release, with 88.26% of the drug released within 20 min. Accelerated stability testing confirmed no significant changes in appearance, softness, or drug release over six months. Conclusion The findings suggest that Kyron T-114-based ion exchange complexation is a robust approach for masking the bitterness of lornoxicam, and MCGs represent a promising, patient-friendly dosage form for fast and effective pain management.
Keywords: Lornoxicam; Medicated Chewing Gum; Taste Masking; Ion Exchange Resin; Kyron T-114; PEG 400.